2015
DOI: 10.3138/jmvfh.2014-04
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive performance improvement in Canadian Armed Forces personnel during deployment

Abstract: Resilience is the ability to adapt and strive under adverse situations. Operational stressors linked to deployment such as isolation, increased workload, sleep deprivation and exposure to life-endangering situations, among others, can decrease resilience and thereby reduce cognitive capabilities of military personnel. We tested the cognitive functioning of Canadian Armed Forces (CAF) military troops (n = 85) using the Cambridge Neuropsychological Test Automated Battery prior to and during their deployment to A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…In relation to ARHL, reduced gray matter volume has also been observed in multiple brain regions, including the temporal lobe [ 44 ], particularly the superior and middle temporal gyri [ 68 ], medial and superior frontal gyri [ 68 ], hypothalamus [ 71 ], and occipital lobe [ 71 ]. Changes in these brain regions and neural networks are associated with impaired cognitive functions including episodic visuospatial memory and learning memory [ 72, 73 ], working memory and executive functions [ 74 ], attention switching [ 75 ], and verbal recognition memory [ 73 ]. Additionally, the cingulo-opercular cortex has been shown to be atrophied in individuals with ARHL as well as in those with impaired episodic memory [ 45 ].…”
Section: Hearing Loss (Age-related Hearing Loss)mentioning
confidence: 99%
“…In relation to ARHL, reduced gray matter volume has also been observed in multiple brain regions, including the temporal lobe [ 44 ], particularly the superior and middle temporal gyri [ 68 ], medial and superior frontal gyri [ 68 ], hypothalamus [ 71 ], and occipital lobe [ 71 ]. Changes in these brain regions and neural networks are associated with impaired cognitive functions including episodic visuospatial memory and learning memory [ 72, 73 ], working memory and executive functions [ 74 ], attention switching [ 75 ], and verbal recognition memory [ 73 ]. Additionally, the cingulo-opercular cortex has been shown to be atrophied in individuals with ARHL as well as in those with impaired episodic memory [ 45 ].…”
Section: Hearing Loss (Age-related Hearing Loss)mentioning
confidence: 99%
“…There are conflicting results from studies measuring the impact of stress from military deployment on cognitive performance. In one study of Canadian peacekeepers, researchers showed increased cognitive performance during deployment, possibly attributable to several factors, and suggested that factors such as motivation and the commitment to the fighting spirit might function to protect against operational stressinduced cognitive decline (Makhani, Akbaryan, & Cernak, 2015). Other studies have shown a decrease in cognitive performance, mainly after periods of intense military stress (Lieberman et al, 2005;Lieberman et al, 2016;Vrijkotte, Valk, Veenstra, & Visser, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Age-associated marked decline in temporal lobe volume (Scahill et al, 2003 ), hippocampal volume (Scahill et al, 2003 ; Raz et al, 2004 ), and prefrontal cortex (Raz et al, 1997 ) have been reported in region-specific imaging studies. Alterations in the above mentioned neural networks are implicated in impaired cognitive functions such as verbal recognition memory (Fletcher and Henson, 2001 ; Henson, 2005 ), episodic visuospatial memory, learning and association ability (Sweeney et al, 2000 ), working memory and executive functions (Owen et al, 1995 , 1996 ), and attention switching (Makhani et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%